2005
DOI: 10.1007/1-4020-3468-7
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Meshfree Methods and Their Programming

Abstract: All Rights Reserved © 2005 SpringerNo part of this work may be reproduced, stored in a retrieval system, or transmitted in any form or by any means, electronic, mechanical, photocopying, microfilming, recording or otherwise, without written permission from the Publisher, with the exception of any material supplied specifically for the purpose of being entered and executed on a computer system, for exclusive use by the purchaser of the work.Printed in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…Heat transfer problem is described by a nonlinear governing Eq. (14) in the fluid region Ω 1 with a linear governing Eq. (18) in the wall region Ω 2 subject to the linear boundary conditions (19)- (23).…”
Section: Solution Of Heat Transfer Problem Using the Modified Methods mentioning
confidence: 99%
See 2 more Smart Citations
“…Heat transfer problem is described by a nonlinear governing Eq. (14) in the fluid region Ω 1 with a linear governing Eq. (18) in the wall region Ω 2 subject to the linear boundary conditions (19)- (23).…”
Section: Solution Of Heat Transfer Problem Using the Modified Methods mentioning
confidence: 99%
“…Heat transfer problem is governed by the dimensionless Eqs. (14) in the fluid region Ω 1 and (18) in the wall region Ω 2 . The boundary conditions are expressed as follows…”
Section: The Energy Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…EFGM has been applied to several engineering problems because of its good performance and accuracy (Singh 2006;Samimi and Pak 2012;Zhang et al 2017). Liu and Gu (2005) found that both the convergence rate and the accuracy of EFGM are higher than bilinear FEM due to higher interpolation accuracy achieved using more support nodes in the shape functions. Also, compared to the meshless RPIM the maximum bandwidth of the final global matrix in EFGM is usually smaller and thus, the computational cost for solving the final system of equation is lower (Liu and Gu 2005).…”
Section: Introductionmentioning
confidence: 98%
“…These methods discretize the computational domain and its boundaries as a set of scattered nodes which can be more conveniently added or removed without disturbing the existing nodal configuration. These methods discretize the governing partial differential equations into a set of algebraic equations involving the nodal values of the problem variables (Liu and Gu 2005). Meshless methods have shown remarkable application potential in various engineering problems including solid mechanics, fluid mechanics, geotechnics and heat conduction (Samimi and Pak 2012;Khoshghalb and Khalili 2010).…”
Section: Introductionmentioning
confidence: 99%